The Effect of Using the Forrest Strategy (A Picture is Worth a Thousand Words) on Developing the Learning of Chest Pass and Changing-Direction Dribbling Skills for Female Students - Omar Hamdi Abdul Rahma (Pubmedia Jurnal Pendidikan Olahraga, 2026)
The research aims to identify the effect of using the Forrest Strategy (A Picture is Worth a Thousand Words) on developing the learning of the chest pass and changing-direction dribbling skills in basketball among female students. The researcher used the experimental approach due to its suitability to the research problem. The research sample consisted of first-year female students in the morning study at the Department of Physical Education and Sports Sciences at Al-Maarif College, totaling (50) students. The researcher used the Statistical Package for the Social Sciences (SPSS) to process the data statistically. The researcher concluded that the Forrest Strategy has a positive effect on developing the learning of the chest pass and changing-direction dribbling skills in a very positive time. The researcher recommends the necessity of applying strategies that use pictures as a visual stimulus to increase students' interaction and attraction.